Analyzing transport in ceramic membranes for organic solvent nanofiltration using Maxwell-Stefan theory. (31st December 2022) - Claessens, Benjamin; Hitsov, Ivaylo; Verliefde, Arne; Nopens, Ingmar
Graphical abstract: Highlights: Transport in membranes containing distinct pores was analyzed using Maxwell-Stefan theory. Diffusive cross-coupling can lead to a shift in rejection of 20 % Viscous flow has an important contribution to the total flux. Thermodynamic non-ideal behavior can lead to large variations in solute rejection. Abstract: Ceramic membranes are highly promising for application in organic solvent nanofiltration (OSN). Unfortunately, the governing molecular transport mechanisms are not yet fully understood. To study the importance of different transport mechanisms, we analyze transport through these membranes using Maxwell-Stefan theory. We show that the total flux is dominated by the viscous contribution, when using Poiseuille's law. Cross-coupling of the order of magnitude observed in liquids, leads to changes in retention of up to 20%. Finally, it was shown that non-ideal thermodynamics in the external liquid phase can explain changes from positive to negative retention when using the same solute in different solvents. This work opens perspectives to choose simpler mass transfer models for process modelling, as well as provides physical insight into which mass transfer mechanisms are important in OSN with ceramic membranes.